Legal Protection for Land Rights Holders in The Context of Land Registration in Indonesia - M. Filusi Ardiansyah; Darwati (Greenation Research & Yayasan Global Resarch National, 2025)
Land registration is commonly regarded as a central instrument for achieving legal certainty in land administration. Through registration, land rights are formally recorded and recognized by the state, providing an administrative framework intended to prevent disputes and to clarify ownership and control over land. In practice, however, an excessive emphasis on administrative registration may narrow the scope of legal protection by equating protection solely with registration status. This approach risks marginalizing land rights that arise from substantive legal relations existing prior to, or outside of, formal registration procedures. In the Indonesian context, land rights may originate from various sources, including long-standing possession, contractual arrangements, inheritance, and recognition under customary law. These rights often develop through social and legal processes that are not immediately reflected in administrative records. When legal protection is defined primarily through registration, the protective function of land law may shift from safeguarding legitimate rights to enforcing procedural compliance. This situation creates tension between legal certainty as an administrative objective and substantive justice as a normative principle. This article examines legal protection for land rights holders within the context of Indonesia’s land registration system by analyzing the relationship between administrative procedures and substantive land rights. Using a normative juridical research method, the study evaluates statutory regulations, legal doctrines, and judicial approaches to assess whether land registration adequately fulfills its protective function. The analysis demonstrates that legal protection should not be confined to registered land alone, but must extend to substantively valid rights that exist beyond formal records. The article argues for a balanced approach in which land registration operates as an administrative instrument that strengthens, rather than restricts, the protection of land rights holders, thereby ensuring that legal certainty and substantive justice are harmonized within Indonesia’s agrarian legal framework.